2010
DOI: 10.1002/acp.1742
|View full text |Cite
|
Sign up to set email alerts
|

Is banner blindness genuine? Eye tracking internet text advertising

Abstract: Over the last decade or so, the Internet has become a privileged media for advertisement. Despite this increase in popularity, several studies suggested that Internet users 'avoid' looking at ads (what is often referred to as the banner blindness phenomena). This conclusion, however, rests mostly on indirect evidence that participants do not remember the ad content. Therefore, it is unclear whether participants actually fixated the ads and how their gaze behaviour is related to memory for the ad. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(86 citation statements)
references
References 38 publications
4
80
0
Order By: Relevance
“…Hervet et al 3 confirm that Internet users avoid looking at banners. This effect was not incidental, but was due to viewers' direct intent to refrain from looking at banners.…”
Section: Problem Statementsupporting
confidence: 51%
See 2 more Smart Citations
“…Hervet et al 3 confirm that Internet users avoid looking at banners. This effect was not incidental, but was due to viewers' direct intent to refrain from looking at banners.…”
Section: Problem Statementsupporting
confidence: 51%
“…The greater the recall, the more effective the campaign is expected to be. A few empirical studies have confirmed that there is a small amount of recall of banner promotions amongst viewers 3,4,13 . However, virtually none of these studies has examined recall in the context of video clips placed on YouTube or in conjunction with viewers' fixation behaviors.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…This information is helpful in capturing the banner blindness phenomenon (i.e., when users ignore provided information) ( (Chatterjee, 2008;Djamasbi, Siegel, & Tullis, 2012a;Djamasbi et al, 2007;Djamasbi & HallPhillips, 2014;Dreze & Hussherr, 2003;Hervet et al, 2011). Studies have shown repeatedly that the same design techniques that can make a perceptual element salient (so that the element can serve as a suitable entry point to the page) can also trigger banner blindness (Djamasbi & Hall-Phillips, 2014).…”
Section: Figure 14 Example Of An Aggregated Aoi Map For Order Of Viewsmentioning
confidence: 99%
“…This effect of user ignoring Internet ads is known as "banner blindness" (Benway, 1998;Benway & Lane, 1998;Hervet, Guérard, Tremblay, & Chtourou, 2011). It is reasonable to expect it to happen as well regarding the ad texts shown at the beginning of internet video ads.…”
Section: Figure 1 Standard Approach In Internet Video Commercialsmentioning
confidence: 99%